Solubility and solubilizing capabilities of aqueous solutions of Extractum Taraxaci e radix cum herba aqu. siccum in light of selected values of general Hildebrand-Scatchard-Fedors theory of solubility - Marczyński Zbigniew; Nowak Sławomira; Jambor Jerzy; Zgoda Marian Mikołaj (Herba Polonica, 2016)
Introduction: The general Hildebrand-Scatchard theory of solubility supplemented by Fedors’ solubility parameter −δ12$- δ ^{{1 \over 2}} $ was used to estimate the real solubility by −log x2 (log of the mole fraction) of phytochemicals contained in Ext. Taraxaci e radix cum herba aqu. siccum. Surface activity of aqueous solution of extracts was determined and quantified – solubilizing capabilities of solutions of cexp. ≥cmc in relation to cholesterol particle size of Ø=1.00 mm, as well as of ketoprofen were defined.